2015
DOI: 10.1016/j.neuropharm.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular and neuroimaging effects of the hallucinogenic serotonin receptor agonist psilocin in the rat brain

Abstract: The development of pharmacological magnetic resonance imaging (phMRI) has presented the opportunity for investigation of the neurophysiological effects of drugs in vivo. Psilocin, a hallucinogen metabolised from psilocybin, was recently reported to evoke brain region-specific, phMRI signal changes in humans. The present study investigated the effects of psilocin in a rat model using phMRI and then probed the relationship between neuronal and haemodynamic responses using a multimodal measurement preparation. Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
3
37
0
Order By: Relevance
“…administered to rats evoked phMRI signal increases in a number of regions, including olfactory and limbic areas and elements of the visual system (Spain et al, 2015). LFP amplitude in response to sensory stimuli was decreased by psilocin administration, concurrently with enhanced CBF.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 94%
See 1 more Smart Citation
“…administered to rats evoked phMRI signal increases in a number of regions, including olfactory and limbic areas and elements of the visual system (Spain et al, 2015). LFP amplitude in response to sensory stimuli was decreased by psilocin administration, concurrently with enhanced CBF.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 94%
“…The alteration in neurovascular coupling reported by Spain et al (2015) might explain, in part, the apparent discrepancy between fMRI and PET findings of decreased CBF (Carhart-Harris et al, 2012) and increased glucose metabolism (Vollenweider et al, 1997b;Gouzoulis-Mayfrank et al, 1999) in human studies with psilocybin and related drugs.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 98%
“…These effects became evident at 6 hours after LPS administration, although similar (non-significant) trends could be observed at the 4 hour time point. It is difficult to assess why significant effects of altered cerebrovascular function are primarily driven by a specific stimulation frequency, although stimulation dependent effects have been previously reported in the literature [40, 41]. Our results suggest the 5Hz stimulation frequency to be particularly salient at driving this effect, and it has been previously reported that in anaesthetised animals this frequency is most effective in driving somatosensory neurovascular responses [41].…”
Section: Discussionmentioning
confidence: 51%
“…injection increased the BOLD contrast in the frontal (orbital) cortex and olfactory nuclei while it was absent after BSCO injection [11]. These diverging results highlight the difficulty interpreting preclinical pharmaco-MRI data [12] complicated by the use of different anesthetic regimes [13] that can introduce potential confounds [14].…”
Section: Introductionmentioning
confidence: 99%